Membangun Desa Pendidikan Melalui Penyuluhan Pendidikan Di Desa Gintung Cilejet Bogor: Pendidikan Melalui Penyuluhan Pendidikan Di Desa Gintung Cilejet Bogor - Ramadhan, Putri Utami (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
This article provides information about community service activities in Gintung village, Cilejet, Bogor. Community service is carried out to answer the problems of the institutional partners of Gintung Cilejet Village, namely trying to educate the community so that they can increase awareness and enthusiasm of the community to continue education. This paper describes by outlining a series of preparatory activities and outlining the service agenda. This activity was carried out with the fostered community, namely the parents of Cilejet Bogor in the Gintung village environment. The conclusion from the implementation of community service still needs to be developed capabilities regarding education in the community so that the interest of the community and parents in education can be carried out.